The Effect of Educational Technology on Learning Facilities on Learning Independence to Improve Learning Outcomes of Building Construction Engineering Students - Djubir R.E. Kembuan; Metsi Daud; Titof Tulaka (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Building engineering education is a discipline that continues to develop along with technological advances. Educational technology, especially the integration of technology in learning facilities, has become an essential aspect in improving the quality of learning at various levels. This study aims to investigate the effect of educational technology on learning facilities on the learning independence of building engineering students and its impact on improving learning outcomes, especially in building construction subjects. This study uses a survey method, with a causal technique. The research sample will consist of final-semester students of the building engineering study program registered at a leading higher education institution. Data will be collected through an instrument in the form of a questionnaire to measure the level of student learning independence, as well as an evaluation test of learning outcomes for building construction subjects. Data analysis will be carried out using descriptive statistical methods to describe student profiles and analyze differences between the experimental and control groups. Furthermore, inferential analysis such as the t-test will be used to identify the effect of educational technology on learning independence and student learning outcomes. It is hoped that this research will result in a deeper understanding of how the integration of educational technology in learning facilities can influence student learning independence in the context of engineering education. The findings from this study can provide guidance for educational institutions in designing more effective learning strategies through the use of educational technology. In addition, this research is also expected to contribute to academic literature related to technical education and the use of technology in learning.